Health system responsiveness and its associated factors for delivery care in public health facilities of West Arsi Zone, Oromia, Ethiopia - Negeso Gebeyehu Gejo; Daniel Yohannes Bedecha; Solomon Seyife Alemu; Maedot Ariaya Haymete; Milion Reta Regasa; Abraham Endale Geleta; Qorinah Estiningtyas Sakilah Adnani (PLoS ONE, 2026)
Background Health System Responsiveness is defined as how well the health system meets the legitimate expectations of the population for the non-health enhancing aspects of the health system. As Ethiopia approaches the conclusion of the Health Sector Transformation Plan-II (HSTP-II), generating evidence on health system responsiveness is critical for evaluating progress and guiding future strategies. However, there remains a scarcity of empirical evidence on health system responsiveness, particularly in the context of delivery care services. Objective The primary aim of this study was to assess the health system responsiveness and its associated factors for delivery care in public health facilities of West Arsi Zone, Oromia, Ethiopia. Methods A health facility-based cross-sectional study was conducted among 617 mothers who gave birth in the selected public health facilities of West Arsi Zone, Oromia Region. Data were collected from 24/02/2025–26/04/2025. Systematic random sampling technique was used to approach study participants. Health system responsiveness was measured using eight domains namely dignity, autonomy, confidentiality, communication, prompt attention, social support, choice and basic amenities each item rated on 1–5 scale. Mothers with median score ≥112 were categorized as having good responsiveness performance for delivery care whereas <112 were considered as poor responsiveness for delivery care. Data was entered and analyzed using SPSS version 25. Both bi-variable and multivariable logistic regression analysis were done to identify association between dependent and independent variables. Crude and adjusted odds ratios with respective 95% confidence intervals were computed and statistical significance was declared at p-value <0.05. Result The overall level of good health system responsiveness for delivery care was found to be 51.4% (95% CI 47.4–55.4). The highest and least performance score was reported in the social support domain (62.9%) and choice domain (51.7%) respectively. Adverse neonatal outcome (AOR = 0.50, 95% Cl (0.31, 0.82), obstetrics complications (AOR = 0.47, 95% Cl (0.26, 0.85), history of admission during current pregnancy (AOR = 0.58, 95% Cl (0.35, 0.96) were factors significantly associated with health system responsiveness. Conclusions More than half of the respondents reported that the overall level of health system responsiveness during delivery was good. Adverse neonatal outcome, obstetrics complications and history of admission during current pregnancy had shown statistically significant association with health system responsiveness for delivery care. Enhancing health system responsiveness during delivery needs targeted investments in infrastructure, continuous training for healthcare providers, and tailored support for women who experience adverse neonatal outcomes or obstetric complications. Strengthening these areas is essential for ensuring respectful, timely, and women centered maternity care.